Evaluation of the Severity of Surgical Endotoxicosis - V. I. Karandin; A. G. Rozhkov; M. I. Tsarev; R. M. Nagayev; P. A. Tikhonov (Общая реаниматология, 2009)
Objective: to develop a scale for rating the severity of surgical endotoxicosis. Subjects and methods. Clinical and laboratory studies were made in 1168 patients with urgent surgical diseases, the course of which was accompanied by severe endogenous intoxication. Multistep statistical processing yielded seven signs that were most important in evaluating the severity of endotoxicosis, which characterized the baseline state of the macroorganism, the toxic potential of endogenous intoxication sources, and the result of the damaging effect of the toxic principle on the most important life support systems. Results. After scoring adaptation of each sign of endogenous intoxication to the significance of other signs, a scale was compiled to evaluate the endotoxicosis severity. The latter was estimated from the number of scores. The authors distinguish three endotoxicosis grades: moderate, severe, and very severe. Conclusion. The scale developed to evaluate the severity of surgical endotoxicosis provides a more objective assessment of the severity of endogenous intoxication since it is based on the consideration of various courses of the pathological process. It is very convenient in clinical use and makes it possible to have not only a single evaluation of the severity of endotoxicosis, but also to characterize its course over time. Key words: evaluation of the severity of endotoxicosis, toxemia gradation.